Architecture of the Northern Outskirts of the Ohrid Archdiocese in the 11th Century - Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2023)
The article is devoted to the history of the architecture of the northern territories of the Ohrid Archbishopric from the time of its foundation (1019), which saw the return of Byzantine power to the Balkans after the victory over the First Bulgarian Empire, to the beginning of the 12th century, when Byzantine building activities in these areas became less intensive while the metropolitan influences gave way to regional trends, which developed within the framework of architectural solutions interpreting the 11th-century samples. Under the first archbishops of Ohrid (John of Debar (1018–1037), Leo of Ohrid (1037–1056)), the construction project began in the different dioceses of the Balkan peninsula, old episcopal cathedrals were renovated, new churches and monasteries were founded. On the part of the Church, the main client was Ohrid, and the administrative center of the Byzantine theme ‘Bulgaria’, the territories returned by the Byzantine in the Balkans, was in Skopje. The wide geography of the renovations and construction in the regions distant from Ohrid lead to the consolidation of the craftsmen from different regions, which would contribute to the diversity of creative ideas and architectural techniques in church building. While in the central and southern dioceses of the Ohrid Archdiocese, the main milestones of the history of architecture are traceable, in the northern dioceses, the names of clients are usually unknown and the dating is inaccurate, although the quality of the buildings often appears to be excellent. This paper aims to clarify the details of church construction to the north of Ohrid (Bulgaria and Serbia) in the 11th century, basing on the architectural peculiarities of the preserved monuments. This research was funded by the Russian Scientific Fund, project no. 20-18-00294-П “Artistic Traditions and Ecclesiastic-Political Ideology in the Medieval Architecture and Art of the Balkans. Macedonian question.”